Hemodynamic Responses to Blood Flow Restriction and Resistance Exercise to Muscular Failure - Libardi, Cleiton Augusto; Catai, Aparecida Maria; Miquelini, Maiara; Borghi-Silva, Audrey; Minatel, Vinicius; Alvarez, Ieda Fernanda; Milan-Mattos, Juliana Cristina; Roschel, Hamilton; Tricoli, Valmor; Ugrinowitsch, Carlos (International Journal of Sports Medicine, 2017)
The aim of the present study was to compare hemodynamic responses between blood flow-restricted resistance exercise (BFR-RE), high-intensity resistance exercise (HI-RE) and low-intensity resistance exercise (LI-RE) performed to muscular failure. 12 men (age: 20±3 years; body mass: 73.5±9 kg; height: 174±6 cm) performed 4 sets of leg press exercises using BFR-RE (30% of 1-RM), HI-RE (80% of 1-RM) and LI-RE (30% of 1-RM) protocols. Systolic (SBP) and diastolic blood pressure (DBP), heart rate (HR), stroke volume (SV), cardiac output (CO) and total peripheral vascular resistance (TPR) were measured on a beat-to-beat continuous basis by a noninvasive photoplethysmographic arterial pressure device. The HI-RE and LI-RE showed higher values (P<0.05) in all of the sets than the BFR-RE for SBP, DBP, HR. Additionally, HI-RE showed higher SBP (4th set) and DBP (all sets) (P<0.05) values than the LI-RE. However, the SV, CO and TPR showed significantly greater values for LI-RE compared to HI-RE and BFR-RE (P<0.05). In conclusion, the results of this study indicate that the BFR-RE promotes a lower hemodynamic response compared to the HI-RE and LI-RE performed to muscular failure.
Keywords: Kaatsu training; resistance training; cardiovascular response; concentric failure